Punción seca en el tratamiento fisioterapéutico de la cefalea tensional. - Achig Tonato, Lizeth Anahí (2024)
This research work focused on tension headache and its physiotherapeutic treatment using the dry needling technique, which consists of inserting needles into myofascial trigger points to relieve muscle tension. Tension headache affects 46% of the world's population and is characterised by headache due to muscle tightness. Given the high prevalence of this neurological condition, the main objective of the research was to evaluate the efficacy of dry needling as a treatment. To this end, a literature review was conducted adopting a documentary correlational approach, using databases such as Pubmed, PEDro, Scopus and Cochrane Library with a meticulous selection of 35 randomised clinical trials in order to present quality information. To ensure methodological adequacy, an assessment was carried out using the PEDro scale. This scale required studies to score 6 or higher to be considered valid within the research framework. An analysis of the selected scientific articles revealed encouraging findings highlighting its effectiveness in reducing the intensity of headache pain, improving cervical range of motion and reducing restriction in the neck region. Although, some results show no significant differences with other therapeutic interventions, most point to short- and long-term improvements in the quality of life of patients suffering from this condition. Research in other muscle conditions, such as chronic neck pain, also supports its impact on condition reduction and muscle improvement. Dry needling can be used alone or in combination with other therapies to optimise the benefits, especially using the rapid entry and exit technique proposed by Hong. However, more studies are needed to understand its action at the molecular level, its comparative and long-term impact, underlining its growing importance as an evolving and valuable therapeutic tool.